The red coloration of Goikoetxe Cave's speleothems (Busturia, Spain): An indicator of paleoclimatic changes. (20th November 2020) - Martínez-Pillado, V.; Yusta, I.; Iriarte, E.; Álvaro, A.; Ortega, N.; Aranburu, A.; Arsuaga, J.L.
Abstract: The most commonly used paleoclimatic proxies in speleothem studies are the carbon and oxygen stable isotopes and the trace elements of calcite. However, assessing the incorporation of other components, such as organic matter, may also be of interest in interpreting and reconstructing the climate during speleothem growth. In this work, the incorporation of humic and fulvic acids derived from overlying soils is proposed as the cause of the red coloration of speleothems from the Goikoetxe Cave (Busturia, Bizkaia). Through the application of petrological studies combined with X-ray fluorescence, UV luminescence, Raman spectroscopy and Fourier-transform infrared spectroscopy (FTIR) analysis, it has been possible to correlate a variation of organic content in the overlying soils and the red coloration, being this stain a main proxy to study and reconstruct the seasonal paleoclimatic parameters during the speleothem formation.